The tourism sector and its role in achieving sustainable tourism development Febrile tourism in Algeria as a model - djekidal, said; rahmoune, adem (Journal of Social Sciences and Humanities, 2023)
Algeria has tourism capabilities and qualifications, especially in the aspect related to febrile tourism, which is distributed throughout the national territory, its febrile waters are characterized by many features and therapeutic properties, all these capabilities represented in the features and therapeutic properties of the existing febrile water, its diversity and spread to various regions and the distinctive coastal strip, all represent significant capabilities to develop tourism in the health and recreational aspect, and provide great investment opportunities in this field. Therefore, this article aims to answer the main question: How can febrile tourism achieve sustainable tourism development in Algeria? For this reason, we were exposed to the concepts related to febrile tourism and its most important conditions, and we tried to collect information about the reality of this type of tourism in Algeria, trying to finally propose the requirements for its development and development in order to rely on it in diversifying the revenues of the Algerian economy, and the most important conclusion we reached through this study: that Algeria is one of the countries that have important components of the Hamoui tourism product, which suffers from many problems in many regions of the country. Which necessitates the reconsideration of such tourism resources.